PERAN FOOD VLOGGER DALAM MEMPERKENALKAN TREN WISATA GASTRONOMI: - - Yulianie, Fatrisia (JURNAL BISNIS HOSPITALITI, 2025)
Food vloggers are individuals who create and share culinary video content through social media to introduce gastronomy tourism trends in an interesting and informative way. This article aims to discuss the role of food vloggers in introducing gastronomy tourism trends as a sustainable tourism trend. The descriptive qualitative method is used to describe the relationship between the events or indications studied in a structured, factual and thorough manner. Data collection is done by collecting literature related to the topic to be analysed, including textbooks, scientific writing articles, YouTube and other legal sources. An interpretative descriptive method was also used to analyse the data.The results show that food vloggers play a role in introducing gastronomy tourism trends, including introducing traditional food as a form of cultural heritage preservation efforts, teaching healthy lifestyles, increasing interest in buying food, and helping to increase sales of small businesses in the culinary field. Food vloggers influence travellers' preferences in choosing a tourist destination. Through their content about gastronomy, they have indirectly supported the creation of sustainable tourism.